Assessing whole genome sequencing variation for Alzheimer's disease in 4707 individuals from the Alzheimer's Disease Sequencing Project (ADSP): Genetics/genetic factors of Alzheimer's disease. (7th December 2020) - Peloso, Gina M.; Wang, Yanbing; Lin, Honghuang; Sarnowski, Chloé; Pitsillides, Achilleas N.; Lim, Elise M.; Beecham, Gary W.; Hamilton‐Nelson, Kara L.; Ramos, Jairo; Martin, Eden R.; Naj, Adam C.; Thornton, Timothy A.; et al.
Abstract: Background: The Alzheimer's Disease Sequencing Project (ADSP) seeks to identify genomic variants contributing to increased risk of and/or protection from Alzheimer's disease (AD) in multi‐ethnic populations. Here we report on statistical modeling considerations and results from 4707 diverse individuals including 2076 non‐Hispanic White, 1030 Black, 1304 Hispanic, and 297 of other ancestry with whole genome sequencing (WGS) in the ADSP. Methods: A total of 4789 individuals were sequenced across 4 sequencing centers and 2 sequencing platforms. Joint calling was carried out by the ADSP data coordinating center GCAD. We evaluated a series of models to explore technical covariate adjustment related to study, sequencing center, and platform and then performed single variant association analysis for AD status adjusting for principal components associated with AD, technical covariates, and a genetic relatedness matrix, limiting to variants with a minor allele count > 30 and a missingness rate ≤ 10%. We also performed gene‐based association of rare (both MAF < 1% and MAF < 5%) coding variants. Results: After quality control, we included over 95 million variants across 4707 individuals (2209 cases, 2498 controls). We replicated association at the APOE locus and identified a locus on chromosome 15 that has a suggestive association with AD status (freq = 0.8%, p‐value = 1 × 10 −7 ). Despite joint genotype calling, adjustment for study, sequencing center and platform are necessary to control type‐I error. In gene‐based tests, we found evidence (p < 0.05) of association for 4 of 8 AD candidate genes with low‐frequency or rare variant associations implicated for AD ( TREM2, ABI3, SORL1, and MAPT ) as well as suggestive associations (P < 5 × 10 −5 ) for seven genes ( ZGRF1 on chr4; C1RL on chr12; NAA30 on chr14; NIPA2 on chr15; and ABCC3, BIRC5 and HIC1 on chr17). Conclusion: We explored covariate models for the WGS data from ADSP and established that despite joint calling, it is necessary to account for technical effects in the model. We found suggestive novel associations with AD status that will require confirmation.